Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Nur Azhana@ Bazilah Binti Haji Mohamad, Siti; Farhana Binti Haji Shahlehi , Syahnur; Siti Nor Suriana Binti Haji Talip , Hajah (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2024)
Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan